1976
DOI: 10.1097/00006842-197605000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Huggins Tumors by Forced Restraint

Abstract: Three experiments demonstrated that chronically administered restraint inhibits the development of DMBA-induced rat mammary tumors. The effect is exhibited in a lower proportion of positive responses, increased latency of tumor development, and lower number of tumors in positive animals when restrained animals are compared with controls. Organ weights failed to show a stress response to restraint. Molar activity data from Experiment III indicated that early in the experiment activity increased among the restra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…It should be noted, however, that although we previously found that 10 inescapable shock sessions had effects that went beyond simply blocking the acute stress-induced tumor enhancement and actually inhibited tumor growth relative to nonshocked controls such an effect was not evident in the present experiment. This is not entirely surprising, in view of the fact that the inhibition we previously observed was quite small and the chronic stress regimens typically employed in studies reporting inhibited tumor growth are considerably more extensive (see [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…It should be noted, however, that although we previously found that 10 inescapable shock sessions had effects that went beyond simply blocking the acute stress-induced tumor enhancement and actually inhibited tumor growth relative to nonshocked controls such an effect was not evident in the present experiment. This is not entirely surprising, in view of the fact that the inhibition we previously observed was quite small and the chronic stress regimens typically employed in studies reporting inhibited tumor growth are considerably more extensive (see [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Methodsmentioning
confidence: 78%
“…With respect to the infra-human investigations, it has been reported that stress may either exacerbate (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) or inhibit (14,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) tumorigenicity. Aside from stress type and social conditions (2,43), two important factors that contribute to these contradictory findings are ability to control stress and chronicity of stress.…”
mentioning
confidence: 99%
“…Henry et al found rapid cancer cell growth in mice kept in isolation, 4 and Newberry et al reported on the effects of electric shock on tumor formation in rats. 5 Riley et al observed the influence of stress on tumor formation and suggested the importance of adrenocortical hormones as its mechanism. 6 In those studies, which used physical stimuli such as strong light stimulation or electric shock, immune function was not directly measured.…”
Section: Discussionmentioning
confidence: 99%
“…If psychological stress interferes with this function, a tumor may be allowed to grow to a size that immune system can no longer deal with easily. [3][4][5][6][7][8][9][10][11][12][13] In recent years, exercise and training have been studied as factors affecting immune responses. [14][15][16][17][18][19][20] We have performed sports rehabilitation for patients with coronary heart disease from the aspect of exercise psychology.…”
mentioning
confidence: 99%
“…Experimental studies carried out on animals proved tumour-inhibitory (Newberry et al 1972(Newberry et al , 1976 as well as tumour-stimulatory effect (Tejwani et al 1991;Kavetsky et al 1966) of psychosocial factors on mammary tumourigenesis. Activation of the hypothalamicpituitary-adrenal system and sympathetic nervous system due to stress results in an increased production of catecholamines and glucocorticoids and consequent negative effects on functions of the immune system.…”
mentioning
confidence: 97%